The innovation-friendly organization : how to cultivate new ideas and embrace the change they bring - Simpson, Anna (Journalist) (Palgrave Macmillan, 2017)
This book explores five cultural traits -- Diversity, Integrity, Curiosity, Reflection, and Connection -- that encourage the birth and successful development of new ideas, and shows how organizations that are serious about innovation can embrace them. Innovation -- the driver of change and resilience -- It is totally dependent on culture, the social environment which shapes how ideas emerge and evolve. Ideas need to breathe, and culture determines the quality of the air. If it's stuffy and lacks flow, then no idea, however brilliant, will live long enough to fulfil its potential. Creating these innovation-friendly conditions is one of the key challenges facing organizations today, and one that is especially difficult for them -- focused as they are on efficiency and control. Innovation, Anna Simpson argues, begins with diversity of thought and attitude: the opposite of conformity and standardisation. Likewise, with ongoing pressures to deliver results before yesterday, how can organizations allow sufficient space for the seemingly aimless process of following interesting possibilities and pondering on the impact of various options? Anna Simpson shows how large organizations can adapt their culture to enable the exchange of different perspectives; to support each person to bring their whole self to their work; to embrace the aimlessness that fosters creative experimentation; to take the time to approach change with the care it deserves, and -- lastly -- to develop the collective strength needed to face the ultimate 'sledgehammer test'.- Resumé vydavatel